Cover Picture: Noble‐Metal‐Free NiS/C3N4 for Efficient Photocatalytic Hydrogen Evolution from Water (ChemSusChem 12/2013). Issue 12 (26th November 2013) - Hong, Jindui; Wang, Yongsheng; Wang, Yabo; Zhang, Wei; Xu, Rong
<x xml:space="preserve">Abstract</x> The front cover image shows how a noble‐metal‐free photocatalyst can contribute to a sustainable Earth through photocatalytic water splitting. Noble metals are widely applied in many photocatalysts, which may limit the potential of these catalysts for large‐scale applications. Hong et al. used NiS as co‐catalyst on metal‐free carbon nitride (C3N4) to construct a noble‐metal‐free photocatalytic system for efficient H2 production under visible light. Even small amounts of NiS can significantly enhance the H2 generation rate in comparison to the native C3N4, resulting in a high quantum efficiency. Details of the method and important parameters can be found in Hong et al.′s Full Paper on page 2263 ff., while more information about the research group is available in the Cover Profile on page 2200.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>